Modelling of hybridoma cell growth profile: article - Uda, Nor Laila; Mohd Pauzi, Syazana; Ahmad, Normadyzah (2018)
This research project is basically a study to develop a model equation for the hybridoma cell growth by mathematical modeling. The mathematical modeling is a tool that specially used for simulates, optimize and control any process. Thus, this method is really suitable to produce an overall model of hybridoma cell growth profile that can predict the characteristics of batch system. Thus, revolution has been made in order to develop the model equations that take into account the factors such as unwanted decline in cell viability, growth rate, culture condition and others that lead to the decreasing of MAB production. In order to develop the model equation, the kinetic of hybridoma cell is being studied. Based on the kinetic study, the growth of hybridoma cell is disturbing by several factors that inhibit the growth. The major factors that affecting the growth cell is substrate limitation and inhibitor production. In this simulation, the hybridoma cell is supplied with glucose and glutamine as the substrate. These substrate act as a carbon source for the growing of the cell. Substrate consumption by the cell during its growth is leading to the formation of inhibitor. However, only glutamine exhaustion being the main factor of growth cessation. The constructed of hybridoma cell growth profile is including all the growth phase except death phase. Based on this simulation, the concentration of ammonia increase proportionally to the decreasing of glutamine concentration. The growth profile of hybridoma cell culture were simulated using an unstructured model in batch mode. All the model equation that involved in the growth of hybridoma has been used and solve by ode45 in Matlab software.